Empreendedorismo feminino no município de Serraria-PB: Características, motivações, desafios e perspectivas - Pereira, Evelly Andina dos Santos (2024)
In recent years, female entrepreneurship has expanded at an accelerated rate. Research on the subject indicates that this increase can be attributed to several factors, such as: the search for self-realization, the need to improve the financial situation, affinity with specific sectors, identification of opportunities in the market, and family influence. However, throughout their journey into entrepreneurship, women still face several challenges. As a general objective, this research seeks to analyze the motivations that led women to undertake in the municipality of Serraria-PB. In order to fully carry out this study, some specific objectives were also defined: to map female entrepreneurship in Serraria-PB; analyze the demographic profile of women entrepreneurs in the Municipality; to identify the main sectors in which women undertake in the municipality; to understand the main challenges and perspectives of female entrepreneurship in the municipality of Serraria-PB. Regarding the objectives and forms, this research is characterized as being descriptive and explanatory, and was developed with a quantitative and qualitative approach. In order to obtain the information necessary for this work, the methodological procedures used were bibliographical survey, documentary study and field research. The data collected were processed and presented using Microsoft Office Excel. Regarding the results, they indicate that women entrepreneurs in the Municipality of Serraria- PB, have several characteristics of entrepreneurial behavior published by SEBRAE. Most of the challenges are related to the historical construction of the role attributed to women, for many years, in our society, with the conciliation between domestic and professional work being the main difficulty raised by female entrepreneurs today. It was also observed that, despite the challenges, women entrepreneurs are satisfied with their occupations, and seek to conquer larger spaces, as they see increasingly promising scenarios in the market and in society as a whole.